Real-world nuclear deterrence : the making of international strategy - Coleman, David G.; Siracusa, Joseph M. (Westport, Conn. : Praeger Security International, 2006)
"Looking at how nuclear deterrence has actually worked rather than how it should theoretically work, Coleman and Siracusa put the problems of nuclear deterrence over the past sixty years into global context and apply historical lessons to the current state of world affairs."--Jacket.
Arming for peace -- Extending nuclear umbrellas -- Credibility gap -- Bridging the gap -- The numbers game -- Keeping the lid on -- The spread of nuclear weapons.
Includes bibliographical references (pages 149-160) and index.
Keywords: Nuclear disarmament; Security, International; Security, International; nuclear strategy -- deterrence; nuclear weapons -- proliferation